UVC, UVB and UVA susceptibility of Phi6 and its suitability as a SARS-CoV-2 surrogate - Laura Weyersberg; Eva Klemens; Jule Buehler; Petra Vatter; Martin Hessling (AIMS Microbiology, 2022)
For SARS-CoV-2 disinfection systems or applications that are based on UVC, UVB or UVA irradiation, it would be desirable to have a SARS-CoV-2 surrogate for tests and development, which does not require a laboratory with a high biosafety level. The bacteriophage Phi 6, an enveloped RNA virus like coronaviruses, is an obvious candidate for such a surrogate. In this study, UVC, UVB and UVA log-reduction doses for Phi6 are determined by plaque assay. Log-reduction doses for SARS-CoV-2 are retrieved from a literature research. Because of a high variability of the published results, median log-reduction doses are determined for defined spectral ranges and compared to Phi6 data in the same intervals. The measured Phi6 log-reduction doses for UVC (254 nm), UVB (311 nm) and UVA (365 nm) are 31.7, 980 and 14 684 mJ/cm2, respectively. The determined median log-reduction doses for SARS-CoV-2 are much lower, only about 1.7 mJ/cm2 within the spectral interval 251–270 nm. Therefore, Phi6 can be photoinactivated by all UV wavelengths but it is much less UV sensitive compared to SARS-CoV-2 in all UV spectral ranges. Thus, Phi6 is no convincing SARS-CoV-2 surrogate in UV applications.